Implementation of a Computer Network Monitoring System Using Icinga Linux-Based Ubuntu Server at SMA N 1 Bengkulu Tengah - Iwan Junaidi; Jusuf Wahyudi; Eko Prasetiyo Rohmawan (Penerbit Jurnal Indonesia, 2022)
One of the network monitoring applications is using Icinga with the Linux Ubuntu server operating system. Icinga is a Linux application or tool that can be used to monitor computer networks. Monitoring computer networks using Icinga can monitor data traffic, network traffic and errors that occur on the network. Monitoring traffic and traffic on the network is displayed in graphical form, making it easier to do the analysis. Meanwhile, in monitoring the errors that occur on the network, they are grouped based on the client and service, so it is easy to see which error occurred from the client and what service was used. In operating the network monitoring system with Icinga using the Linux Ubuntu server operating system, the use of computer resources is very small, which is less than 20%.